LST1/A is a myeloid leukocyte-specific transmembrane adaptor protein recruiting protein tyrosine phosphatases SHP-1 and SHP-2 to the plasma membrane - Draber, Peter; Stepanek, Ondrej; Hrdinka, Matous; Drobek, Ales; Chmatal, Lukas; Mala, Linda; Ormsby, Tereza; Angelisova, Pavla; Horejsi, Vaclav; Brdicka, Tomas (The Journal of biological chemistry, 2012)
Transmembrane adaptor proteins are membrane-anchored proteins consisting of a short extracellular part, a transmembrane domain, and a cytoplasmic part with various protein-protein interaction motifs but lacking any enzymatic activity. They participate in the regulation of various signaling pathways by recruiting other proteins to the proximity of cellular membranes where the signaling is often initiated and propagated. In this work, we show that LST1/A, an incompletely characterized protein encoded by MHCIII locus, is a palmitoylated transmembrane adaptor protein. It is expressed specifically in leukocytes of the myeloid lineage, where it localizes to the tetraspanin-enriched microdomains. In addition, it binds SHP-1 and SHP-2 phosphatases in a phosphotyrosine-dependent manner, facilitating their recruitment to the plasma membrane. These data suggest a role for LST1/A in negative regulation of signal propagation.
Keywords: Primary Cell Culture; buněčná membrána; signální transdukce; U937 buňky; Membrane Proteins; myeloidní buňky; transport proteinů; tyrosinfosfatasa nereceptorového typu 6; Signal Transduction; Humans; HeLa buňky; Protein Tyrosine Phosphatase, Non-Receptor Type 11; Jurkat buňky; Protein Transport; Molecular Sequence Data; intracelulární signální peptidy a proteiny; molekulární sekvence - údaje; sekvence aminokyselin; tyrosinfosfatasa nereceptorového typu 11; Jurkat Cells; lidé; HEK293 Cells; U937 Cells; Amino Acid Sequence; Intracellular Signaling Peptides and Proteins; primární buněčná kultura; Major Histocompatibility Complex; HeLa Cells; HEK293 buňky; Pseudopodia; Myeloid Cells; Plakins; plakiny; hlavní histokompatibilní komplex; membránové proteiny; Cell Membrane; terciární struktura proteinů; Protein Tyrosine Phosphatase, Non-Receptor Type 6; Protein Structure, Tertiary; pseudopodia